Prevalence of Chagas Disease in a U.S. Population of Latin American Immigrants with Conduction Abnormalities on Electrocardiogram. - Mahmoud I Traina; Salvador Hernandez; Daniel R Sanchez; Jalal Dufani; Mohsin Salih; Adieb M Abuhamidah; Wilman Olmedo; Jason S Bradfield; Colin J Forsyth; Sheba K Meymandi (Public Library of Science (PLoS), 2017)
Chagas disease (CD) affects over six million people and is a leading cause of cardiomyopathy in Latin America. Given recent migration trends, there is a large population at risk in the United States (US). Early stage cardiac involvement from CD usually presents with conduction abnormalities on electrocardiogram (ECG) including right bundle branch block (RBBB), left anterior or posterior fascicular block (LAFB or LPFB, respectively), and rarely, left bundle branch block (LBBB). Identification of disease at this stage may lead to early treatment and potentially delay the progression to impaired systolic function. All ECGs performed in a Los Angeles County hospital and clinic system were screened for the presence of RBBB, LAFB, LPFB, or LBBB. Patients were contacted and enrolled in the study if they had previously resided in Latin America for at least 12 months and had no history of cardiac disease. Enzyme-linked immunosorbent assay (ELISA) and immunofluorescence assay (IFA) tests were utilized to screen for Trypanosoma cruzi seropositivity. A total of 327 consecutive patients were screened for CD from January 2007 to December 2010. The mean age was 46.3 years and the mean length of stay in the US was 21.2 years. Conduction abnormalities were as follows: RBBB 40.4%, LAFB 40.1%, LPFB 2.8%, LBBB 5.5%, RBBB and LAFB 8.6%, and RBBB and LPFB 2.8%. Seventeen patients were positive by both ELISA and IFA (5.2%). The highest prevalence rate was among those with RBBB and LAFB (17.9%). There is a significant prevalence of CD in Latin American immigrants residing in Los Angeles with conduction abnormalities on ECG. Clinicians should consider evaluating all Latin American immigrant patients with unexplained conduction disease for CD.